PENGARUH STRUKTUR MODAL DAN EFISIENSI OPERASIONAL TERHADAP KINERJA KEUANGAN PADA PT CHITOSE INTERNASIONAL TBK PERIODE 2015-2024 - Sausana Sabila; Gatut Dradjad Purwoko (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to analyze the effect of Capital Structure and Operational Efficiency on Financial Performance at PT Chitose Internasional Tbk during the period 2015–2024. Financial performance is measured using Return on Assets (ROA), capital structure is measured by the Debt to Equity Ratio (DER), and operational efficiency is measured by Total Asset Turnover (TATO). This research employs a quantitative associative method with a time-series approach over a ten- year period. The data used are secondary data in the form of the company’s financial statements obtained from the Indonesia Stock Exchange (IDX). The data analysis techniques include descriptive statistics, classical assumption tests, , simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results show that, partially, capital structure has a negative and significant effect on financial performance, as indicated by a t-value greater than the t-table value (-5,263 > 1.89458) and a significance value of 0,001 < 0.05. Meanwhile, operational efficiency partially has a positive and significant effect on financial performance, with a t-value greater than the t-table value (5,608 > 1.89458) and a significance value of 0,001 < 0.05. Furthermore, based on the F-test results, the F- value is greater than the F-table value (20,532 > 4.74) with a significance value of 0,001 < 0.05, indicating that capital structure and operational efficiency simultaneously have a significant effect on the financial performance of PT Chitose Internasional Tbk. The coefficient of determination shows that 81,3% of the company’s financial performance can be explained by capital structure and operational efficiency, while the remaining 18,7% is influenced by other factors.